POLYNUCLEOTIDE ENCODING ADRENOCORTICOTROPIC HORMONE, AND RELATED COMPOSITION AND METHOD THEREOF - SHAN, Yongqiang; LIU, Rui; YANG, Fan; LI, Zhenjian (2025)
Provided is a nucleic acid molecule encoding adrenocorticotropic hormone, or a functional fragment or variant thereof. The present invention further relates to a composition containing the nucleic acid molecule, comprising a lipid nanoparticle, and a related treatment method and use for treating or preventing rheumatic diseases (including but not limited to gout inflammation), lung diseases, ophthalmologic diseases, kidney diseases or neurological diseases (including but not limited to infant spasms and multiple sclerosis) in a subject. L'invention concerne une molécule d'acide nucléique codant pour l'hormone adrénocorticotropique, ou un fragment fonctionnel ou un variant de celle-ci. La présente invention concerne en outre une composition contenant la molécule d'acide nucléique, comprenant une nanoparticule lipidique, et une méthode de traitement associée et une utilisation pour traiter ou prévenir des maladies rhumatismales (y compris, mais sans s'y limiter, une inflammation liée à la goutte), des maladies